2017
DOI: 10.11606/s1518-8787.2017051006675
|View full text |Cite
|
Sign up to set email alerts
|

Depression and unemployment incidence rate evolution in Portugal, 1995–2013: General Practitioner Sentinel Network data

Abstract: OBJECTIVE Quantify, for both genders, the correlation between the depression incidence rate and the unemployment rate in Portugal between 1995 and 2013.METHODS An ecological study was developed to correlate the evolution of the depression incidence rates estimated by the General Practitioner Sentinel Network and the annual unemployment rates provided by the National Statistical Institute in official publications.RESULTS There was a positive correlation between the depression incidence rate and the unemployment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
1
4
0
6
Order By: Relevance
“…Our results on the impact of chronic conditions seem to point in an opposite direction: in fact, while in the simple model almost all the chronic conditions were risk factors for unemployment, only depression was retained in the full multiple model, together with the presence of physical disability as an outcome from injuries. The finding about depression as factor related to unemployment is in line with recent literature showing that the relationship between unemployment and depression is significant among adults [ 58 , 59 , 60 ]. This factor may act as a risk factor for unemployment but also as a consequence of unemployment and has been show that this population may benefit from employment and mental health focused interventions [ 60 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our results on the impact of chronic conditions seem to point in an opposite direction: in fact, while in the simple model almost all the chronic conditions were risk factors for unemployment, only depression was retained in the full multiple model, together with the presence of physical disability as an outcome from injuries. The finding about depression as factor related to unemployment is in line with recent literature showing that the relationship between unemployment and depression is significant among adults [ 58 , 59 , 60 ]. This factor may act as a risk factor for unemployment but also as a consequence of unemployment and has been show that this population may benefit from employment and mental health focused interventions [ 60 ].…”
Section: Discussionsupporting
confidence: 88%
“…Os resultados do presente estudo corroboram a existência de uma correlação positiva entre desemprego e depressão na população portuguesa, observada pelo nosso grupo de investigação até 2013. 9 Este trabalho de monitorização pretendia verificar se a correlação observada se mantinha após a crise, ou seja, no período de recuperação económica. Com a integração de dados referentes a anos posteriores (2016, 2017 e 2018), anos de recuperação económica com menores taxas de desemprego, este estudo demonstrou uma redução da taxa de incidência de depressão, em ambos os sexos.…”
Section: Discussionunclassified
“…Colocou-se, então, a hipótese de que o aumento observado da taxa de incidência de depressão em Portugal se pudesse encontrar relacionado com a situação de crise económica. 9 Até ao início da pandemia de COVID-19, Portugal estava a recuperar lentamente da crise, com um aumento progressivo da taxa de crescimento real do PIB, desde 2014 com valores positivos, e uma diminuição da taxa de desemprego. 10 A condução de estudos sobre o impacto de crises económicas na saúde mental é cíclica, tendo-se verificado uma tendência de aumento durante o período de recessão e imediatamente após.…”
Section: Introductionunclassified
“…Fourth, the study results indicated that the employment status of adult children was signi cantly related to their depression. Economically inactive men have a higher risk of depression than women [34][35][36], and long-term unemployment is highly related to depression in comparison with short-term unemployment [37]. Finally, we found that adult children's BMI was associated with their depression, which is consistent with previous studies showing that those who are underweight and those who are severely obese are more likely to be depressed than those who are of normal weight and those who are overweight (U-shaped relationship) [38,39].…”
Section: Discussionmentioning
confidence: 99%